KOMBINASI WAKTU DEFOLIASI ENTRES DAN MODEL SAMBUNG PUCUK TERHADAP PERTUMBUHAN BIBIT CACAO (Theobroma cacao, L) - ROSMAITI ROSMAITI; IWAN SAPUTRA (Universitas Lancang Kuning, 2019)
Abstract The aim of the study was to get the interaction between the time of entries defoliation and shoot grafting model that gave the best Cacao seedling growth. The treatment design consists of two factors, namely the defoliation time of the entries and the top graft model. The time of entries defoliation consists of 4 defoliation times, entres defoliation at the connection (W1), entres defoliation 3 days before connection (W2), entres defoliation 6 days before connection (W3), and entres defoliation 9 days before connection (W4). The connection factor model is tested by two connection models, namely, connecting gap (S1), and diagonal connection (S2). The environmental design used is a randomized block design in factorial patterns. Parameters of cacao seedling growth observed were the percentage of live seedlings (%), time of shoot buds (days), shoot length (cm), shoot diameter (cm), and a number of leaf buds (strands). The results of this research are that there is no interaction between the treatment combination of all observed parameters. The best time for defoliation is 9 days before connection. The defoliation model used shows different results that are not real.